PENGARUH KEPEMIMPINAN DAN PENGEMBANGAN KARIR DENGAN KINERJA - Andri Susilo; Sri Huzaetul Aeni (The Asia Pacific Journal Of Management Studies, 2018)
This study aims to determine the effect of: (1) leadership; (2) career development; on employee performance. This research was conducted at Banten Province Bawaslu Employees. The method used is a quantitative associative survey research method using correlational analysis techniques, with a population of 43 people. Seals in this study use booring sampling as such, then the entire population is used as a sample of research, as many as 43 respondents were analyzed using the Statistical Product and Service Solution Program using SPSS Version 22 assistance. 0.021 leadership means that the leadership variable has a positive effect on performance variables, and career development values obtained significance 0.027 means that career development variables have a positive effect on performance variables, and based on the f test simultaneously obtained value results, that the significance value is 0,000. From the results of the significance above that the significance value is less than 0.05. So there is a significant influence between leadership and career development on performance, with a strong correlation coefficient. The conclusion is that leadership and career development variables together have a positive and significant effect on performance variables. This shows that the greater the leadership and career development factors of employees are met, the higher the level of performance.